Enhanced quality of nutrition services during antenatal care through interventions to improve maternal nutrition in Bangladesh, Burkina Faso, Ethiopia, and India - Nguyen, Phuong Hong; Tran, Lan M.; Kachwaha, Shivani; Sanghvi, Tina; Mahmud, Zeba; Zafimanjaka, Maurice G.; Walissa, Tamirat; Ghosh, Sebanti; Kim, Sunny S. (International Society of Global Health, 2025)
Background Quality antenatal care (ANC) services are critical for maternal health and nutrition. Information on the quality of nutrition interventions during ANC is scarce in low- and middle-income countries. We examined the effects of intensified maternal nutrition interventions during ANC on service readiness, provision of care, and experience of care and assessed the inter-relationships between the dimensions of quality.